Full-Body Motion From a Single Head-Mounted Device: Generating SMPL Poses From Partial Observations - Dittadi, Andrea; Dziadzio, Sebastian; Cosker, Prof. Darren; Lundell, Ben; Cashman, Tom; Shotton, Jamie (International Conference on Computer Vision 2021, 2021)
The increased availability and maturity of head-mounted and wearable devices opens up opportunities for remote communication and collaboration. However, the signal streams provided by these devices (e.g., head pose, hand pose, and gaze direction) do not represent a whole person. One of the main open problems is therefore how to leverage these signals to build faithful representations of the user. In this paper, we propose a method based on variational autoencoders to generate articulated poses of a human skeleton based on noisy streams of head and hand pose. Our approach relies on a model of pose likelihood that is novel and theoretically well-grounded. We demonstrate on publicly available datasets that our method is effective even from very impoverished signals and investigate how pose prediction can be made more accurate and realistic.